Fodder shrubs for improving livestock productivity and smallholder livelihoods in Africa - Franzel, Steven; Carsan, S.; Lukuyu, Ben A.; Sinja S; Wambugu C (Elsevier, 2014)
Fodder trees are important feed sources for livestock in a wide range of farming systems in Africa. Researchers, extension services and farmers have developed and promoted fodder tree practices in many different countries and contexts. Fodder trees are particularly important in the highlands of Eastern Africa, where over 200 000 smallholders plant them, mainly to feed dairy cows. They can meet production shortages in times of extreme climatic conditions such as droughts. Fodder trees are easy to grow, require little land, labor or capital, have numerous by-products and often supply feed within a year after planting. Key challenges constraining the uptake of fodder trees include limited species appropriate to different agro-ecological zones, shortages in seed and that farmers lack knowledge and skills needed to grow them.